Activated mast cells in skeletal muscle can be a potential mediator for cancer‐associated cachexia. Issue 4 (18th May 2021) - Widner, D. Brooke; Liu, Chun; Zhao, Qingxia; Sharp, Sarah; Eber, Matthew R.; Park, Sun H.; Files, D. Clark; Shiozawa, Yusuke
Abstract: Background: Eighty per cent of United States advanced cancer patients faces a worsened prognosis due to cancer‐associated cachexia. Inflammation is one driver of muscle atrophy in cachexia, and skeletal muscle‐resident immune cells could be a source of inflammation. This study explores the efficacy of cancer activated skeletal muscle‐resident mast cells as a biomarker and mediator of cachexia. Methods: Individual gene markers for immune cells were assessed in a publicly available colon carcinoma cohort of normal ( n = 3), moderate cachexia ( n = 3), and severe cachexia ( n = 4) mice. Lewis lung carcinoma (LL/2) cells induced cachexia in C57BL/6 mice, and a combination of toluidine blue staining, immunofluorescence, quantitative polymerase chain reaction, and western blots measured innate immune cell expression in hind limb muscles. In vitro measurements included C2C12 myotube diameter before and after treatment with media from primary murine mast cells activated with LL/2 conditioned media. To assess translational potential in human samples, innate immune cell signatures were assessed for correlation with skeletal muscle atrophy and apoptosis, dietary excess, and cachexia signatures in normal skeletal muscle tissue. Gene set enrichment analysis was performed with innate immune cell signatures in publicly available cohorts for upper gastrointestinal (GI) cancer and pancreatic ductal adenocarcinoma (PDAC) patients (accession: GSE34111 and GSE130563, respectively). Results: Individual innate immunity genes (TPSAB1 and CD68) showed significant increases in severe cachexia (weight loss > 15%) mice in a C26 cohort (GSE24112). Induction of cachexia in C57BL/6 mice with LL/2 subcutaneous injection significantly increased the number of activated skeletal muscle‐resident degranulating mast cells. Murine mast cells activated with LL/2 conditioned media decreased C2C12 myotube diameter ( P ≤ 0.05). Normal human skeletal muscle showed significant positive correlations between innate immune cell signatures and muscle apoptosis and atrophy, dietary excess, and cachexia signatures. The mast cell signature was up‐regulated (positive normalized enrichment score and false discovery rate ≤ 0.1) in upper GI cachectic patients ( n = 12) compared with control ( n = 6), as well as in cachectic PDAC patients ( n = 17) compared with control patients ( n = 16). Conclusions: Activated skeletal muscle‐resident mast cells are enriched in cachectic muscles, suggesting skeletal‐muscle resident mast cells may serve as a biomarker and mediator for cachexia development to improve patient diagnosis and prognosis.